The Soviet Accounting Bulletin, 1973-1983 - David Alexander (Journal of Accounting and Management Information Systems (JAMIS), 2013)
The Soviet Accounting Bulletin was published from 1973 to 1983. It provided rare and fascinating direct insight into the role, function and position of the bookkeeper/accountant in the Soviet system, both in theory, e.g. through Lenin's writing, and in practice, e.g. through extensive quotations in the words of the bookkeepers themselves. It was largely written by Derek Bailey, who had not only the contacts and language ability to obtain and translate material, but also the knowledge to write critical and informative commentaries thereon. This paper gives extensive extracts, preserving both the wording and the ethos of the original material as much as possible. The unifying theme is the life and role of the Soviet bookkeeper in all its aspects. Such an existence embraced real tensions, which we highlight, juxtapose and discuss.
Keywords: M40; M49; 650; Soviet; Accounting; Bookkeeper; Uchet